Can leisure and entertainment lifestyle promote health among older people living alone in China?—A simultaneous equation approach - Qin, Yinghua; Liu, Jingjing; Wang, Rizhen; Qi, Xinye; Jiang, Shengchao; Li, Jiacheng; Guo, Pengfei; Wu, Qunhong (Frontiers in Public Health, 2022)
Abstract Objectives With the surging number of elderly living alone, their lifestyles and health status arouse people’s increasing concern. This study aims to investigate whether leisure and entertainment life (LEL) can improve the multi-dimensional health among the elderly living alone, and try to identify the latent mechanisms among them. Method By extracting data from the Chinese General Social Survey (CGSS), we established a simultaneous equations model, consisting of ordinary least squares regression (OLS), two-stage least squares (2SLS), and the mediating effect model, to measure the relationship between leisure and entertainment with multidimensional health of the elderly living alone from China. Results The elderly living alone in China reported relatively a better mental health status (3.64 ± 1.07), followed by physical health (3.41 ± 1.26) and social health (2.75 ± 1.18). In the OLS model, LEL can significantly improve the social health of elderly living alone (β = 0.054, P < 0.01), followed by physical health (β = 0.042, P < 0.01) and mental health (β = 0.027, P < 0.01). After endogenous tests from 2SLS and robustness tests, we found that more active leisure and entertainment life were associated with higher levels of physical health and mental health. However, leisure and entertainment life had no significant effect on the improvement of the social health of the elderly living alone. Using the mediation analysis, exercise efficacy played partial mediates between LEL and physical health, LEL and mental health, and the ratio is 19.75%, and 24.85%, respectively. So did positive life attitudes, and mediated partially between LEL and physical health, LEL and mental health, with ratios of 10.65% and 26.83%, respectively. Conclusion Our findings suggested that leisure and entertainment was significantly associated with better physical and mental health for the elderly living alone in China, and were mediated by exercise efficacy and positive attitude to life. Promoting more leisure and recreational activities, upgrading the exercise efficacy as well the positive life attitude were necessary health promotion measures for the well-being of the elderly living alone in active aging policies.